R&D Cooperatives and Market Collusion: A Global Dynamic Approach - Jeroen Hinloopen; Grega Smrkolj; Florian Wagener (Tinbergen Institute, 2016)
We present a continuous-time generalization of the seminal R&D model of d'Aspremont and Jacquemin (American Economic Review, 1988) to examine the trade-off between the benefits of allowing firms to cooperate in R&D and the corresponding increased potential for product market collusion. We consider all trajectories that are candidates for an optimal solution as well as initial marginal cost levels that exceed the choke price. Firms that collude develop further a wider range of initial technologies, pursue innovations more quickly, and are less likely to abandon a technology. Product market collusion could thus yield higher total surplus.
Keywords: D43; D92; L13; L41; O31; O38; 330; Antitrust policy; Bifurcations; Collusion; R&D cooperatives; Spillovers